The lion king 2 : simba's pride [video recording]. (Pasig City : Viva Video Inc., 2004)
All the power and majesty of animation's greatest achievement- Disney's academy award winning film, The lion king-return for The lion king 2: Simba's pride, the final volume of the lion king trilogy. Now, in this new special edition, meet Kiara and Kovu, the newest generation of the pride, experience the power of "Upendi" - which means "love" and enjoy more of Timon and Pumbaa's hilarious antics!